Corporate Governance and Shariah Governance: Assessing from Takaful Operators in Malaysia - Nurul Nazlia Jamil; Ainulashikin Marzuki; Avylin Roziana Mohd Ariffin; Anita Ismail (Human Resource Management Academic Society, 2024)
Vol 12, Issue 3